1995
DOI: 10.1542/peds.96.5.914
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Lactate Correlates With Intracranial Hemorrhage in Neonates Treated With Extracorporeal Life Support

Abstract: Objectives. To correlate the initial and maximal lactate levels with the occurrence of intracranial hemorrhage (ICH) and survival in patients treated with extracorporeal life support (ECLS). Design. Retrospective chart review. Setting. Pediatric intensive care unit. Patients. Eighty-two neonatal patients placed on ECLS for respiratory failure due to sepsis, meconium aspiration, or persistent pulmonary hypertension of the newborn. Measurements. The ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Lactate levels may serve as a surrogate for disease severity and may be associated with a more pronounced coagulopathy at ECMO initiation. The correlation between high lactate levels upon ECMO initiation and ICH has previously been described by Grayck et al, who studied 82 neonatal ECMO patients and found higher lactate levels in neonates that developed ICH and In non-survivors 19 . High lactate levels compromise the coagulation system and if uncorrected, this impairment may contribute to ICH progression in ECMO patients 20 .…”
Section: Discussionsupporting
confidence: 52%
“…Lactate levels may serve as a surrogate for disease severity and may be associated with a more pronounced coagulopathy at ECMO initiation. The correlation between high lactate levels upon ECMO initiation and ICH has previously been described by Grayck et al, who studied 82 neonatal ECMO patients and found higher lactate levels in neonates that developed ICH and In non-survivors 19 . High lactate levels compromise the coagulation system and if uncorrected, this impairment may contribute to ICH progression in ECMO patients 20 .…”
Section: Discussionsupporting
confidence: 52%
“…Lactate accumulation has been observed in the brains of patients following ICH ( 15 ). Studies have explored the prognostic value of lactate in patients with ICH and illustrated that higher lactate levels are associated with 90-day mortality and poor outcomes in patients with ICH ( 16 , 17 ). Additionally, albumin, the most abundant protein in the plasma, is the main determinant of the balance of plasma oncotic pressure and the main modulator of fluid distribution between body compartments.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated serum lactate levels have been correlated with rates of mortality (12). Studies that investigate the role of serum lactate in clinical entities such as shock, extracorporeal life support, myocardial infarction, and trauma (13,14) have shown a strong correlation between high blood lactate levels and an increased risk of morbidity and mortality. An absolute lactate level or range that correlates with morbidity or mortality has not been defined, although the peak lactate level may indicate low cardiac output or reduced tissue oxygen extraction.…”
mentioning
confidence: 99%